In Vivo Stress Behavior in Cemented and Screw-Retained Five-Unit Implant FPDs - Donald W. Sheets, Jr., DMD;1 Toru Okamoto, DDS, PhD;2 Leonore C. Dijkgraaf, (Journal of Prosthodontics, 2006)
The purpose of this study was to use the rat air pouch model of facsimile synovium to evaluate oxidative stress as a primary mechanism in the pathogenesis of degenerative temporomandibular joint (TMJ) disease.